Simple transanal total mesorectal resection versus laparoscopic transabdominal total mesorectal resection for the treatment of low rectal cancer: a single-center retrospective case-control study - Yang, Wei-Feng; Chen, Wenbin; He, Zijian; Wu, Zixin; Liu, Huilong; Li, Guanwei; Li, Wang-Lin (Frontiers in Surgery, 2023)
To evaluate the efficacy and safety of simple TaTNE in the treatment of low rectal cancer compared with laparoscopic transabdominal TME.We collected patients with low rectal cancer admitted to our hospital between January 2019 and November 2021 who received simple TaTME or laparoscopic transabdominal TME. The main outcome was the integrity of the TME specimen.Secondary outcomes were the number of lymph nodes dissected, intraoperative blood loss, operative time, surgical conversion rate, Specimen resection length, circumferential margin (CRM), and distal resection margin (DRM), complication rate.In addition, the Wexner score and LARS score of fecal incontinence were performed in postoperative follow-up.Pathological tissues were successfully resected in all patients. all circumferential margins of the specimen were negative. Specimen resection length was not statistically significant (9.94±2.85 VS 8.90±2.49,P>0.05). The incidence of postoperative complications in group A (n=0) was significantly lower than that in group B (n=3) (P>0.05). There was no significant difference in operation time between group A and group B (296±60.36 VS 305±58.28, P>0.05). Among the patients with follow-up time less than 1 year, there was no significant difference in Wexner score and LARS score between group A and group B (P>0.05). However, in patients who were followed up for more than 1 year, the Wexner score in group A (9.25±2.73) was significantly lower than that in group B (17.36±10.95) and was statistically significant (P <0.05).For radical resection of low rectal cancer, Simple TaTME resection may be as safe and effective as laparoscopic transabdominal TME, and the long-term prognosis may be better.